SPORTS COACHES’ PROFICIENCY AND ATHLETES’ SPORTS SUCCESS BASED ON ATHLETES’ TYPE IN SOUTH-SOUTH NIGERIA - CHRISTOPHER OSAS ALUYA; PROF. SAMUEL O. AIBUEKU (International Studies Journal, 2025)
The research looked at the connection between South-South Nigerian athletes' sports accomplishments and the proficiency of their coaches, paying special emphasis to the type of athlete. A sample of 1,402 athletes was chosen by multistage sampling from a population of 4,669 athletes spread across six states using a correlational design. Data was collected using the Coaches' Competence and Athletes' Sports Achievement Questionnaire (CCASAQ), which has a Cronbach's alpha of 0.81. The data was analysed using Fisher's Z statistics and Pearson correlation at a significance level of 0.05. The findings showed a statistically significant, positive, and modest correlation between athletes' sports accomplishments and the skill of their coaches. The study, which was informed by the theories of self-determination and social cognition, discovered a moderately substantial relationship between the accomplishments of athletes and the competency of their coaches, with the relationship being noticeably stronger among student-athletes. The reason for the discrepancy is that student-athletes usually receive more individualised and prolonged instruction. In order to increase athletes' performance across a range of sporting categories, the study highlights the crucial role that coaching competency plays in affecting sports performance and suggests on-going professional development programs for coaches. This study adds to the body of knowledge by shedding light on the relationship between coaching proficiency and athletic success, especially in the Nigerian environment.